PERBEDAAN PENGARUH MEDIA EDUKASI KESEHATAN REPRODUKSI MENGGUNAKAN LEAFLET DAN FILM TERHADAP PENGETAHUAN DAN SIKAP SISWA-SISWI SMAN 3 DEPOK TAHUN 2014 - Hasyati Dwi Kinasih, (2014)
Adolescence is a time of transition from children to adults where the period is characterized by the growth and development of sexual maturity is also affected so many reproductive health problems. It required education on reproductive health in order to increase knowledge and attitudes on adolescents. Reproductive health education media used can be as diverse as leaflet and film media used in this study and the use of both media aimed to analyze the differences in the effect of both increasing the knowledge and attitude about reproductive health of the students of SMAN 3 Depok. This research use a quasi experimental study with stratified random sampling technique. The study was conducted to 300 students of SMAN 3 Depok as samples. The data obtained were statistically tested with a Wilcoxon test to look at differences in knowledge and attitude of students before and after counseling with the media given leaflets and films with the results of a probability value p = 0.000 at α = 0.05 to p < α which means that there are significant differences between knowledge and attitudes before and after counseling with leaflet and film media. In addition, data was also tested with the Mann Whitney test statistic on the value of α = 0.05 to see the difference in the effect of educational leaflet and film media to increased knowledge and attitude of the students and the results obtained probability value of p = 0.038 for the variable knowledge and p = 0.006 for attitudinal variables. Because the values of two variables p < α means that there are significant differences between the leaflet and film media on knowledge and attitudes of the students of SMAN 3 Depok. From the results obtained it can be concluded that the film media is more influential in improving the knowledge and attitude of the students of SMAN 3 Depok.